2003
DOI: 10.1002/ana.10786
|View full text |Cite
|
Sign up to set email alerts
|

Defeating migraine pain with triptans: A race against the development of cutaneous allodynia

Abstract: For many migraine patients, triptan therapy provides complete pain relief in some attacks but not in others. Here, we tested whether the success of triptan therapy is hindered in the presence of cutaneous allodynia (pain resulting from a nonnoxious stimulus to normal skin), a phenomenon we previously described develop gradually during the course of the migraine attack in more than 70% of patients. We studied migraine patients repeatedly on three visits to the clinic: in the absence of migraine (baseline), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
513
4
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(560 citation statements)
references
References 23 publications
31
513
4
11
Order By: Relevance
“…This result confirms that triptans cannot abolish already established central sensitization, 5,7 but it also suggests that triptans cannot abolish already established peripheral sensitization.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This result confirms that triptans cannot abolish already established central sensitization, 5,7 but it also suggests that triptans cannot abolish already established peripheral sensitization.…”
Section: Discussionsupporting
confidence: 72%
“…12 However, it has recently been shown that the triptans are less effective in aborting a migraine attack if the central sensitization is already established. 5 The combination of indomethacin, prochlorperazine, and caffeine (IndoProCaf) is a drug of well-established use in Italy with a recognized efficacy and a good level of safety in the acute treatment of migraine. Each active ingredient of IndoProCaf has specific antimigraine properties.…”
mentioning
confidence: 99%
“…Considering also the different responses to triptans in migraine, with or without allodynia [4], we may suppose that allodynia and osmophobia help distinguish two migraineur subgroups with different disabilities, different therapeutic responses and perhaps different follow-ups; therefore, we think that it is useful to ask patients with migraine about these two features. Allodynia and osmophobia could be predictive factors for a negative evolution of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Triptans can abort pain prior to the development of central sensitisation, but not after allodynia has been established [4]. Unfortunately, when central sensitisation and allodynia are established, pharmacological agents only attenuate migraine symptoms but do not stop the underlying pathophysiologic process.…”
Section: Marcello Fanciullacci Francesco De Cesarismentioning
confidence: 99%